Magic of lines II : line illustrations by global artists - Chu, Kuang (Middlesex, UK : CYPI Press, 2016)
" Line plays an essential role in illustration composition. It can be used in sketching the contours of shapes to create illusions of space, and it can convey feelings to cloth works of art with distinctive styles. With its strong new style, The Magic of Lines II displays the line's rich diversification in forms and its vehement and unique expressiveness in illustrated works. This book is a collection of works by excellent artists from around the globe. It presents elaborate introductions and interviews and gathers nearly 200 works by 27 leading artists whose main means of expression is lines. Enlarged images of certain sections are included to enrich the book's content"--Publisher's description.
Sequel to 2014 edition.
Keywords: Line (Art); Illustrators -- History -- 21st century